Gaming for change - exploring systems thinking and sustainable practices through complexity-inspired game mechanics - Thomas-Julian Irabor; Peegdsom Simplice Assomption Yameogo; Lucille Perrin; Benoit Pétré; Daniel Faulx; Simon R. Ruëgg; Nicolas Antoine-Moussiaux (Humanities & Social Sciences Communications)
Abstract This study examines how a serious game—Tipping Point—can improve systems thinking and sustainable decision-making. Building on earlier research in sustainability education, it addresses gaps in linking theory with hands-on practice by testing whether game-based learning can shift players from short-term, individual goals to long-term, collective strategies. An inductive, phenomenological approach was used with 70 participants from three academic programs in Belgium. Data were gathered via written reflections, focus group discussions, and facilitator observations during multiple game sessions. In Tipping Point, players made decisions on resource management, house construction, renovation, and waste removal, simulating real-world sustainability challenges. The game sessions showed that participants initially pursued immediate, self-centered actions but gradually shifted toward cooperative, future-focused strategies. Repeated gameplay and debriefings helped players recognize the benefits of resource sharing and adaptive planning, leading to a clearer understanding of the trade-offs between short-term gains and sustainable outcomes. This work demonstrates the potential of game-based learning to build essential skills in systems thinking and sustainable decision-making. The results support the inclusion of serious games in educational programs as a way to better prepare individuals for addressing complex social, economic, and environmental challenges, while suggesting useful avenues for further research.